Understanding Malaysian household waste separation: An extended theory of planned behavior / Nurul Hidayana Mohd Noor ... [et al.] - Mohd Noor, Nurul Hidayana; Mustafa, Muhammad Amirul Shahmir; Mohd Saharom, Nur’ Ain; Shamsol Kamal, Nor Syafiqah Syahirah (Universiti Teknologi MARA, Perak, 2022)
The strike of COVID-19 in March 2020 has caused the implementation of the Movement Control Order (MCO) and lockdown by the Malaysian government. As a consequence, MCO has changed Malaysians' norms. Many Malaysians have become compulsive online buyers and the food waste issue has occurred due to the problem of over-purchasing. This study intends to extend the Theory of Planned Behaviour (TPB) in influencing waste separation among households. This study investigates the influence of descriptive norms, personal norms, and cognition of consequences towards the intention to separate waste. This research used a quantitative online survey and convenience sampling. A final and valid sample of 300 households was analysed using Pearson correlation. This research indicates that descriptive norms and cognition of consequences significantly influence the intention of Malaysian households to separate waste. On the other hand, personal norms do not have an influence on the waste separation intention. Therefore, the government, local authorities, related agencies, and non-governmental organisations (NGOs) should ensure that the Malaysian public is aware of the importance of protecting the environment. This study is unique since many studies have focused on the recycling intentions and behaviour and this study is among new and pioneer studies that apply the extended TPB in investigating the determinants of household waste separation in Malaysia during the pandemic COVID-19.